2013
DOI: 10.1101/lm.030270.113
|View full text |Cite
|
Sign up to set email alerts
|

Reexposure to the amnestic agent alleviates cycloheximide-induced retrograde amnesia for reactivated and extinction memories

Abstract: We investigated whether reexposure to an amnestic agent would reverse amnesia for extinction of learned fear similar to that of a reactivated memory. When cycloheximide (CHX) was administered immediately after a brief cue-induced memory reactivation (15 sec) and an extended extinction session (12 min) rats showed retrograde amnesia for both memories. CHX did not produce amnesia for a moderate extinction session (6 min). Re-administering CHX before testing reversed the amnestic effect for both memories (i.e., t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
4
17
2
Order By: Relevance
“…We can conclude that our findings are in stark contrast with the existing literature on post-reactivation amnesia in rats, in which systemic administration of MDZ (Table 1), PROP (Table 2), or CYCLO (Haubrich et al, 2015) has been shown to induce amnesia for contextual fear memories or other types of memories (Briggs & Olson, 2013;Dębiec & Ledoux, 2004;Flint & Marino, 2007;Przybyslawski et al, 1999;Robinson & Franklin, 2010;Taubenfeld et al, 2009). These studies report large effect sizes, and no failures to replicate have been published when using methodologies similar to the ones adopted in the current experiments (i.e., using systemic drug administration after unreinforced re-exposure to the conditioned context in rats).…”
Section: Discussioncontrasting
confidence: 99%
“…We can conclude that our findings are in stark contrast with the existing literature on post-reactivation amnesia in rats, in which systemic administration of MDZ (Table 1), PROP (Table 2), or CYCLO (Haubrich et al, 2015) has been shown to induce amnesia for contextual fear memories or other types of memories (Briggs & Olson, 2013;Dębiec & Ledoux, 2004;Flint & Marino, 2007;Przybyslawski et al, 1999;Robinson & Franklin, 2010;Taubenfeld et al, 2009). These studies report large effect sizes, and no failures to replicate have been published when using methodologies similar to the ones adopted in the current experiments (i.e., using systemic drug administration after unreinforced re-exposure to the conditioned context in rats).…”
Section: Discussioncontrasting
confidence: 99%
“…If the second dose of cycloheximide inhibited processing, one could argue that this caused the shorter cross latencies due to the inability to process fear. However, previous research from our lab, using the same second dose of cycloheximide 20 minutes prior to testing and a similar paradigm, showed recovery of an old reactivated fear memory that increased latency scores and the recovery of an extinction of fear memory that decreased latency scores (Briggs & Olson, 2013). Thus, because of the differential effects, it is unlikely that any inhibited processing caused by the treatment can account for the low latencies observed by the reexposed cycloheximide group.…”
Section: Discussionmentioning
confidence: 61%
“…That is, extinction is attenuated if the cue-only exposure is conducted in a separate context from original conditioning or testing. Additional evidence for extinction as new learning comes from research demonstrating that extinction is susceptible to disruption using a number of amnestic agents, including hypothermia (Briggs & Riccio, 2007;Fava & Riccio, 2014), ethanol (Bisby et al, 2015;Lattal, 2007), an NMDA antagonist (Falls, Miserendino, & Davis, 1992), a sodium channel blocker (Eisenberg, Kobilo, Berman, & Dudai, 2003), and protein synthesis inhibitors (Berman & Dudai, 2001;Briggs & Olson, 2013;Pedreira & Maldonado, 2003;Power, Berlau, McGaugh, & Steward, 2006;Sandusky, Flint, & McNay, 2012;Vianna, Szapiro, McGaugh, Median, & Izquierdo, 2001). That extinction can be disrupted and forgotten while leaving the original acquisition memory intact suggests that extinction involves new learning that forms a separate competing memory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, a longer 30-minute exposure did produce extinction, rendering extinction susceptible to amnesia, leaving the original fear memory intact. That is, with short exposure durations amnesia for a reactivated memory was obtained, however with longer exposure amnesia for extinction was observed [see also 18,19,25,26]. Thus, it appears that the dominant trace active during the time of amnestic treatment is the important factor in determining amnesia.…”
Section: Introductionmentioning
confidence: 99%